225k views
1 vote
Can you please send me the

User Carmoreno
by
5.4k points

1 Answer

1 vote

we have the expression


(106+15i)/(-8+3i)

step 1

Multiplicate numerator and denominator by the conjugate of denominator

so


(106+15i)/(-8+3i)\cdot(-8-3i)/(-8-31)

Remember that

i^2=-1

so


(106+15i)/(-8+3i)\cdot(-8-3i)/(-8-31)=(-848-318i-120i-45i^2)/(64-9i^2)
\begin{gathered} (-848-318i-120i-45i^2)/(64-9i^2)=(-848-438i+45)/(64+9) \\ \\ =(-438i-803)/(73) \end{gathered}

Simplify


(-438i-803)/(73)=(-438i)/(73)-(803)/(73)=-6i-11

the answer is

-6i-11

User Damon Baker
by
4.6k points